Quantifying the Relative Importance of Key Drivers of Landing Page - Viswanathan, P. K.; Swaminathan, T. N. (Indian Journal of Marketing, 2017)
In the world of Internet surfing, the first impression of a webpage is formed by the quality of its Landing Page. It is important as it drives the visitor's perception of the contents of the website. It influences visitors to make a purchase, sign up for a newsletter, or do any other activity that may be the purpose of the site. In e-commerce / commercial portals, triggering click to action (CTA) has become all the more important. This study aimed to assess the key drivers or attributes responsible for enhancing the quality of the landing page as well as for triggering click to action (CTA) through preference decomposition approach. Each page consists of various elements or combinations of elements such as title, body, font face, background theme or color, etc. This research study attempted to quantify the relative importance of the key attributes that would maximize the click through rate (CTR) apart from attracting visitors to the page and influence them to traverse through the webpage or website entirely. It emerged from our study that high colour impact (31.57%), image in banner (26.31% ), relevant theme (15.78%), and flashing relevant ads (15.78% ), in that order, were the key drivers.